DRUG UTILIZATION EVALUATION IN DIABETIC PATIENTS IN A TERTIARY CARE TEACHING HOSPITAL: A PROSPECTIVE OBSERVATIONAL STUDY - myreddy, kasi jagadeesh (Journal of Drug Delivery and Therapeutics, 2014)
Drug utilization is defined as the study of usage of drugs in the community or race. The drug utilization evaluation studies (DUES) aims to analyse the rationality of drugs usage and also describes the nature and drug exposure, and may also help to identify non-adherence problems. In a developing country India, Diabetes mellitus is a clinical issue in population. The type II diabetes mellitus has more prevalence among Indian individuals. The objectives of the study were to evaluate the Prescription pattern, assessment of Drug Interactions and To evaluate the occurrence of Diabetes with other comorbidities. A prospective observational study was conducted in Basaveswara Medical College Hospital and Research Centre, Chitradurga. The study was conducted for a period of six months from December-2012 to May-2013.Out of 201 patients, 101 patients were males and 100 patients were females and large numbers of diabetic patients were between the age group of 51-60 year. in case of prescription pattern, more number of patients prescribed with Monotherapy (68.15%), among the monotherapy, Insulin was largely prescribed (76.64%). Among the combination therapy Glimiperide with Metformin was largely prescribed. Total 154 prescriptions found with Drug Interactions. Out of all DI’s, Moderate drug interactions are more (42.78%), followed by Minor (19.4%) and Major Drug Interactions (14.42%). The present study concluded sulfonylureas was the most commonly prescribed oral hypoglycaemic drug in this hospital followed by combination with biguanides (i.e. Glimepiride with metformin)..Among insulin therapy, human actrapid (regular) was most commonly prescribed drug. Key words: Drug utilization, Hyperglycaemia, Drug Interactions, Prescribing pattern